Analisis Tingkat Efisiensi Bank Umum Syariah di Indonesia pada Era Masyarakat Ekonomi Asean (MEA) - Rona Rosida; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Theepurpose of this researchbis to identify the levelnof efficiency of SharianCommercial Banks in thenASEAN Economic Community (AEC) era and also to identify the policies that cankbe taken by Sharia Commercial Banks to improve their efficiency byiusing the DEA methodiand VRS modelnwith an intermediation approach. Furthermore, this research uses 6 Sharia Foreign Exchange Commercial Banks as samples. This research showsjthat the averagehSharia Commercial Bank hasibeen quite efficientiin carrying out its role as an intermediary institution. Sharia Commercial Banks that experience fluctuations in their efficiency are BNIS and BRIS. Whereas other Sharia Commercial Banks have consistently achieved optimum efficiency. Policy recommendations that can be implemented by Sharia Commercial Banks, especially for Sharia Commercial Banks that havejnot yet reachedkthe optimum levelkof efficiency, to increase their level of efficiency are by controlling and allocating optimal resources and by further increasing their output capacity by maintaining existing inputs.